Linking Declared and Undeclared Water Demands with Climate Variability to Assess the Sustainability of the Aculeo Lagoon in Central Chile - Vergara-Egert, P; Alaniz-Baeza, A; Barrios-Saravia, A; Hidalgo-Corrotea, C (Elsevier B.V., 2025)
Climate change has exacerbated water scarcity in Mediterranean zones worldwide, leading to the loss of water bodies. An iconic case is Aculeo Lagoon, the largest natural lagoon in the Chilean Mediterranean zone, which went completely dry in 2018 but was replenished in 2024 after two consecutive wet years which produced flooding in Central Chile. This study aims to unravel the contribution of declared (water rights allocation) and undeclared water extractions in the basin that led to the drying process of Aculeo lagoon. Water extractions from declared and undeclared water uses (swimming pools and dams), were identified. Then, water extractions were quantified through an annual water balance analysis considering three scenarios of water efficiency and considering the runoff inflow. Statistical analyses were applied to estimate the relationship between lagoon surface area, water use, runoff inflow, and the final water balance. Results revealed that declared water use increased from 229.1 l/s in 2010 to 429.4 l/s in 2024 (+87.4 %). Undeclared water use from swimming pools increased from 1.2 ± 0.5 l/s to 6.2 ± 2.4 l/s (+421 %) between 2010 and 2024, while water used by farm dams increased from 0.27 ± 0.1 l/s to 28.50 ± 7.6 l/s. Total water use increased from 230.6 ± 0.1 l/s to 464.1 ± 11.7 l/s during the study period (+101.3 %). The lagoon surface area was not significantly correlated with annual runoff and net balance but was negatively correlated with water use (p-value = 0.017). These results suggest that the behavior of the Aculeo lagoon was most likely associated with water consumption. We believe that the lagoon may completely dry out again in the coming years, as water use in the basin has not decreased, while surface runoff may experience decreasing patterns due to climate change forcings. This study provides new methodological tools for exploring the synergistic effect of climate change and water overuses. © 2025 Elsevier B.V.
Keywords: Climate change; Mediterranean zone; Sustainability; Water management; Water scarcity